O-L08 Prognostic value of body morphometrics in patients undergoing surgery for hilar cholangiocarcinoma. (16th December 2021) - Gilbert, Timothy; Quinn, Marc; Bird, Nick; Diaz-Nieto, Rafael; Jones, Robert; Fenwick, Steven; Malik, Hassan; Gordon-Weeks, Alex
Abstract: Background: Hilar cholangiocarcinoma is an aggressive cancer with poor prognosis. Complex pre-operative workup is required prior to major surgery that frequently involves an extended hepatectomy with biliary reconstruction and is associated with high levels of post-operative morbidity and mortality. Tools to predict overall and disease-specific outcome are required to better tailor pre-habilitation interventions and selection of patients for surgery. Here we investigate whether body morphometrics are associated with disease-free and overall survival. Methods: Consecutive patients undergoing resection of hilar cholangiocarcinoma were identified within a prospectively maintained database in a single institution. The CoreSlicer web-based app was used to calculate body morphometrics at the L3 vertebral level (muscle, visceral and subcutaneous fat areas) from portal-phase CT images. Median cut-offs defined patient groups and height-normalised morphometric values were compared at diagnostic and subsequent pre-operative imaging. Multivariate analysis was used to identify relationships between body morphometrics at time of diagnosis, changes in body morphometrics in the pre-operative period and outcome. Results: Body morphometrics were assessed in 88 patients at the time of diagnosis. Of these patients, 53 underwent re-staging enabling an assessment of change in body morphometrics during the pre-operative period. Men displayed significantly higher muscle area, visceral fat and lower subcutaneous fat than women. High visceral fat area at diagnosis was an independent predictor of reduced overall survival (HR 1.81, 95% CI 1.1-3.3, P = 0.03), whilst loss of skeletal muscle area during the pre-operative period was an independent predictor of reduced disease-free survival (HR 2.90, 95% CI 1.0-8.8, P = 0.05). Patients with higher visceral fat at diagnosis also appear at increased risk of post-hepatectomy liver failure (PHLF) and experience significantly higher 30-day mortality than those without elevated visceral fat. Conclusions: The presented results identify potential value in assessing body morphometrics as a prognostic tool in patients undergoing surgery for hilar cholangiocarcinoma. External validation of these findings in larger patient cohorts will help to determine whether this can be utilised to guide pre-habilitation interventions and appropriately select patients for surgery.